IMPLEMENTING THEMATIC SONGS IN TEACHING VOCABULARY SKILLS FOR ELEMENTARY STUDENTS IN TAMAN BACA MASYARAKAT KUDI GUNUNG CUNIL BANYUMAS - Purwaningsih, Dyah Raina; Sari, Rosdiana Puspita; Purwandari, Gigih Ariastuti (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2017)
The discussion on English vocabulary teaching is not a new thing, especially when it is about the technique and method used in the teaching-learning process. The purpose of this paper is to disseminate the result of community service experience in teaching vocabulary for elementary students by using thematic songs. This activity is conducted to different grade students that belong to a reading community called Taman Baca Masyarakat Kudi that is located in one of Banyumas subdistricts. The use of songs is in accordance with our community service purpose that is to motivate the students that English is fun to learn. Teaching vocabulary especially to young learners should be fun and and the teacher should avoid monotonous activities. However, some teachers are still stuck in the convensional method, for example by asking students to memorize a stack of vocabulary items without taking into account student’s boredom in doing such task. Songs are considered effective to be used in teaching children because they can trigger children’s creativity and curiousity especially in dealing with vocabulary acquisition.Keyword: teaching,vocabulary, thematic songs, English PENERAPAN LAGU-LAGU BERTEMA DALAM PENGAJARAN KOSAKATA UNTUK SISWA SEKOLAH DASAR DI TAMAN BACA MASYARAKAT KUDI GUNUNG CUNIL BANYUMASAbstrakPembahasan tentang pengajaran kosakata bahasa Inggris bukanlah hal yang baru, terutama bila menyangkut teknik dan metode yang digunakan dalam proses belajar mengajar. Makalah ini bertujuan menyebarkan pengalaman dalam pengabdian kepada masyarakat dalam mengajarkan kosa kata dengan menggunakan lagu-lagu bertema untuk siswa sekolah dasar. Aktivitas ini dilaksanakan dalam sekelompok siswa sekolah dasar yang berasal dari kelas berbeda yang tergabung dalam komunitas baca bernama Taman Baca Masyarakat Kudi yang terletak di salah satu kecamatan Banyumas. Penggunaan lagu sesuai dengan tujuan pelayanan masyarakat kita, yaitu untuk memotivasi siswa bahwa bahasa Inggris itu menyenangkan untuk dipelajari. Lagu dianggap efektif untuk digunakan dalam mengajar anak-anak karena bisa memicu kreativitas dan rasa ingin tahu anak-anak terutama dalam kaitannya dengan proses pemerolehan kosakata.Kata kunci: pengajaran, kosakata, lagu tematik, bahasa Inggris